Alexithymia in Amyotrophic Lateral Sclerosis and Its Neural Correlates - Benbrika, Soumia; Doidy, Franck; Carluer, Laurence; Mondou, Audrey; Buhour, Marie-Sonia; Eustache, Francis; Viader, Fausto; Desgranges, Béatrice (Frontiers in Neurology, 2018)
Introduction: Amyotrophic lateral sclerosis (ALS) is a severe neurodegenerative disease that causes progressive and extensive motor deficits. Patients may also have cognitive impairments or alteration of emotional processing. difficulty correctly identifying the emotions of others. Very few studies, however, have looked at deficits in how they experience their own feelings (alexithymia). Methods: We assessed alexithymia in 28 patients with ALS using the 20-item Toronto Alexithymia Scale (TAS-20), comparing them with a control group matched for sex, age and education level. We took into account both the total score of the TAS-20 and its three subscores corresponding to the three dimensions of alexithymia: Difficulty Identifying Feelings (DIF), Difficulty Describing Feelings (DDF), and Externally Oriented Thinking (EOT). Patients also underwent a neuropsychological assessment and anatomical magnetic resonance imaging (MRI) in order to correlate cognitive performances and gray matter volume and level of alexithymia. Results: On average, ALS subjects had a significantly higher total score and DIF sub-score of the TAS-20 than controls indicating an increased alexithymia in patients. Total and DIF Scores correlated significantly and negatively to gray matter volume of the prefrontal cortex, right superior temporal pole and parahippocampal gyri. No correlations were found between scores on executive functions and those on the TAS-20. Conclusion: the first stage of one’s own emotional processing seems to be affected in ALS independently of executive dysfunction. This trouble seems to be underpinned by cerebral regions that are well known to be both implicated in alexithymia in healthy subjects and altered in ALS.